Mechanical properties of a tropical fruit - Niew, Yan Ling (2016)
Packaging is a necessity to many industries especially when the transportation of goods is involved. Many industries strive towards optimization and hence, it is important to either continue to improve the performance of existing packaging materials or to discover new resources. One potential resource that has yet to be explored is the natural fibre of durian shells. This is motivated from the intactness of the durian fruits despite them dropping from heights of up to 50 metres when they are ripe. Hence, the purpose of this study is to investigate the energy absorption capabilities of durian shells and determine whether they are a suitable source of packaging materials. The durian is first investigated as a whole and subsequently in their individual components mainly the thorns and its mesocarp. The durian shell properties such as its toughness, density and specific energy absorbed were calculated from the quasi static compression tests. The thorns were subjected to axial compression loadings whereas the mesocarp samples were subjected to both lateral and axial loadings. It was concluded that the thorns had a minimum impact on energy absorption as compared to its mesocarp counterpart. Also, the alignment of the fibres in the mesocarp was parallel to the axial direction of loading and hence it absorbed more energy in the axial direction. The mesocarp samples were also subjected to heat treatment to investigate any change in properties and it was found that the mesocarp samples lose their turgidity and toughness when dried. Also, in general, the capabilities of energy absorption increased with an increase in volume, ceteris paribus. However, these conclusions might not be comprehensive enough as the samples tested were mere small cut outs of the entire shell and it might not represent the properties of the entire durian accurately. This is because it is believed that its spherical structure that encompasses the entire fruit plays a significant role in absorbing energy and thus it will be inaccurate to extrapolate it directly to its full volume.